Easily understanding on post-harvest handling subject through video-based learning: a study on Agriculture Students at UiTM Melaka, Malaysia - Jumintono, Jumintono; Devi, Fransiska Sinta; Emmy Hamidah, Emmy Hamidah; Wahyu Santoso, Wahyu Santoso (Auricle Global Society of Education & Research, 2021)
Video-based learning (VBL) is an attractive teaching approach that comprehensively prepares students to solve problems. This study explores the effectiveness of video-based learning media in increasing students' knowledge about post-harvest handling. The research method used is a quantitative descriptive survey. Research respondents were year three students of Undergraduate Plantation Technology and Management from Universiti Teknologi Mara (UiTM) Melaka, Jasin Campus. Random distribution of questionnaires using Google form. Samples were taken based on a purposive sampling technique, namely those taking post-harvest handling courses. The survey was conducted using research instruments to measure students' understanding before and after being given treatment (watching videos). Data analysis with ttest (α = 5%) shows differences in pre-test and post-test scores, namely differences in knowledge before watching videos and watching videos. The results show that the post-test result score is higher than the pretest score and can be categorized as high. This treatment indicates that students can understand well the subjects of post-harvest handling. The t-test result shows that the application of VBL had a significant effect on students' understanding of post-harvest handling. Video-based learning can be used as an alternative to learning in the era of the industrial revolution 4.0 to increase students' knowledge of a learning topic.